Innovative Solid-State Recycling of Aluminum Alloy AA6063 Chips Through Direct Hot Rolling Process - Mauro Carta; Noomane Ben Khalifa; Pasquale Buonadonna; Rayane El Mohtadi; Filippo Bertolino; Mohamad El Mehtedi (Metals)
In this paper, the feasibility of an innovative solid-state recycling process for aluminum alloy AA6063 chips through direct rolling is studied, with the aim of offering an environmentally sustainable alternative to conventional recycling processes. Aluminum chips, produced by milling an AA6063 billet without the use of lubricants, were first compacted using a hydraulic press with a 200 kN load and subsequently heat-treated at 570 °C for 6 h. The compacted chips were directly hot-rolled through several successive passes at 490 °C. The bulk material underwent the same rolling schedule to allow comparison of the samples and assess the process, in terms of mechanical properties and microstructure. All the rolled samples were tested by tensile and microhardness tests, whereas the microstructure was observed by an optical microscope and the EBSD-SEM technique. The fracture surface of all tested samples was analyzed by SEM. Recycled samples exhibited good mechanical properties, comparable to those of the bulk material. In particular, the bulk material showed an ultimate tensile strength of 218 MPa, in contrast to 177 MPa for the recycled chips, and comparable elongation at break. This study demonstrates that direct rolling of compacted aluminum chips is both technically feasible and has environmental benefits, offering a promising approach for sustainable aluminum recycling in industrial applications within a circular economy framework.